Interest in brief resistance training workouts among older US adults with and without mobility disability - Jordan D. Kurth; Christopher N. Sciamanna; Margaret K. Danilovich; David E. Conroy; Kathryn H. Schmitz; Matthew Silvis; Liza S. Rovniak; Robert Creath; Ema V. Karakoleva (PLoS ONE, 2025)
Background/Objectives Resistance training (RT) improves strength and physical function; however, only 35% of older adults meet national guidelines for muscle strengthening activities. Though time is often noted as a barrier to physical activity participation, little is known about the interest of older adults in brief RT programs. This study compared preferences for brief, more frequent vs longer, less frequent RT programs. Methods A nationwide survey was conducted among 611 US adults aged 65 and over. Preference for either (1) a traditional (45 minutes per session, three days per week) RT program or (2) a short (5 minutes per session, daily) RT program was compared. Results Overall, 2.2 times as many older adults preferred the daily 5-minute RT program versus the traditional RT program (68.4% v. 31.6%). Preference for the brief, daily RT program was 5.3 times higher among adults with difficulty walking (84.2% v. 15.8%) than for the traditional RT program. Conclusion Preference for a daily 5-minute RT program is significantly higher than for traditional 45-minute, three times weekly programs. This difference is larger in older adults who have serious difficulty walking or climbing stairs. Significance/Implications Brief daily RT options may help engage older adults in RT at a population level, particularly those with poorer health and mobility disability. Future investigations should evaluate differences in uptake, adherence, and outcomes from two RT programs of varying durations and frequencies.